Serologic characterization of human Ia antigens using B cell lymphoid lines - Bodmer, J; Young, D; Jones, E; Barnstable, C; Goodfellow, P; Bodmer, W; Svejgaard, A; Thomsen, M; Trucco, M; Curtoni, E; Festenstein, H; Sachs, J (1977)
This article discusses the detection of Ia antibodies in HLA-typing sera using B-cell lymphoid lines, the grouping of the sera into five preliminary clusters, and their associations with D-locus specificities.